Contemporary critical theorists : from Lacan to Said - Simons, Jon, 1961- (Edinburgh University Press, 2004)
This volume covers semiotics and discourse analysis, deconstruction, feminism, queer theory, and postmodernism. Individual chapters focus on each of the following theorists: Lacan, Althusser, Barthes, Derrida, Levinas, Kristeva, Irigaray, Cixous, Foucault, Lyotard, Deleuze and Guattari, Baudrillard, Bourdieu, Habermas, Jameson, and Said. Each chapter provides biographical information and details about the thinker's intellectual contexts, an explanation of key concepts, a discussion of the ways in which their theory has been applied, and suggestions for further reading.